1921 Fla. Laws 307 - (:unkn) unknown (My University, 1921)
An Act to Protect the Birds and Wild Life of the County of Orange and State of Florida and to Prevent the Hunting of Same During the Closed Season, ch. 8781, § 2: Prohibited anyone carrying a gun in the woods, field, or on the water such as those generally used for hunting game or having a gun during the closed season. Violators subject to arrest, fine, and imprisonment.
Keywords: HUNTING REGULATION